2019
DOI: 10.1021/acsnano.9b07763
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Single Atoms on Monolayer Transition Metal Dichalcogenides for Ultrafast Hydrogen Evolution

Abstract: Large scale implementation of electrochemical water splitting for hydrogen evolution requires cheap and efficient catalysts to replace expensive platinum. Molybdenum disulfide is one of the most promising alternative catalysts but its intrinsic activity is still inferior to platinum. There is therefore a need to explore new active site origins in molybdenum disulfide with ultrafast reaction kinetics and to understand their mechanisms. Here, we report a universal cold hydrogen plasma reduction method for synthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
126
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 68 publications
4
126
0
Order By: Relevance
“…2D transition-metal dichalcogenides (TMDs) have been intensively investigated for numerous unexplored physics and device applications. [1][2][3][4][5] Among the various methods for synthesizing TMD monolayers, chemical vapor deposition (CVD) has been widely used for high-quality TMD monolayers over a large area. [6][7][8][9] The optical and electrical properties of CVD-grown While a hexagonal WS 2 monolayer, grown by chemical vapor deposition, exhibits distinctive patterns in photoluminescence mapping, segmented with alternating S-vacancy (SV) and W-vacancy (WV) domains in a single crystal, the formation mechanism for native alternating defect domains remains unresolved to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2D transition-metal dichalcogenides (TMDs) have been intensively investigated for numerous unexplored physics and device applications. [1][2][3][4][5] Among the various methods for synthesizing TMD monolayers, chemical vapor deposition (CVD) has been widely used for high-quality TMD monolayers over a large area. [6][7][8][9] The optical and electrical properties of CVD-grown While a hexagonal WS 2 monolayer, grown by chemical vapor deposition, exhibits distinctive patterns in photoluminescence mapping, segmented with alternating S-vacancy (SV) and W-vacancy (WV) domains in a single crystal, the formation mechanism for native alternating defect domains remains unresolved to date.…”
Section: Introductionmentioning
confidence: 99%
“…2D transition‐metal dichalcogenides (TMDs) have been intensively investigated for numerous unexplored physics and device applications. [ 1–5 ] Among the various methods for synthesizing TMD monolayers, chemical vapor deposition (CVD) has been widely used for high‐quality TMD monolayers over a large area. [ 6–9 ] The optical and electrical properties of CVD‐grown TMDs are still limited by inherent point defects; vacancies of chalcogen and metal atoms are unavoidably generated in the crystal, and these vacancies play a key role in determining carrier scattering, [ 10 ] light‐emitting efficiency, [ 11,12 ] doping effects, [ 13 ] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Here, different synthetic strategies for single metal atom-doped MoS 2 are summarized and discussed ( Fig. 2a-f [36][37][38][39][40][41]).…”
Section: Synthesismentioning
confidence: 99%
“…In addition to thermal annealing, plasma treatment is another effective way for introducing single atoms, which shows a strong reducibility and the ability to dissociate chemical bonds between metal cations and anions at a low temperature in a metal complex to generate metal single atoms. For example, Luo et al [39] reported the synthesis of single metal atoms confined in MoS 2 monolayers by a cold hydrogen plasma reduction method (Fig. 2d).…”
Section: Post-treatment Synthesismentioning
confidence: 99%
“…In general, platinum (Pt) group materials are recognized as the benchmark HER electrocatalysts. However, the high cost, low earth abundance, and poor stability greatly hinder their widespread application [9–11] . Accordingly, it is extremely urgent to explore highly active and earth‐abundant electrocatalyst for HER.…”
Section: Introductionmentioning
confidence: 99%